The composition of the gut microbiome differs among community dwelling older people with good and poor appetite. Issue 2 (13th February 2021) - Cox, Natalie J.; Bowyer, Ruth C.E.; Ni Lochlainn, Mary; Wells, Philippa M.; Roberts, Helen C.; Steves, Claire J.
Abstract: Background: Anorexia of ageing is common and important in the development of sarcopenia in older individuals. Links have been proposed between the gut microbiota and sarcopenia. Disordered gut function is also recognized in anorexia of ageing, but how this may relate to resident gut microbiota is unexplored. Understanding this relationship may provide a basis for novel interventions for anorexia of ageing and sarcopenia. This study explores compositional differences of the gut microbiota between community dwelling healthy older adults with good or poor appetite, and associated differences in sarcopenia. Methods: We assessed appetite by the Simplified Nutritional Appetite Questionnaire (SNAQ) in members of the TwinsUK cohort aged ≥65 years. Using a pool of 776 individuals with existing microbiome data estimated from 16S rRNA sequencing data, we identified 102 cases (SNAQ score < 14) (95% female, mean age 68 years) matched to controls (SNAQ > 14) on body mass index, gender, age, diet, calorie consumption, frailty, antibiotic use, socio‐economic status, and technical variables to minimize confounding microbiota associations. Species abundance and diversity, compositional differences, and paired differences in taxa abundance were compared between cases and controls. Additionally, we compared case and controls for sarcopenia as measured by muscle mass (appendicular lean mass/height 2 ) and strength (chair stand time in seconds). Results: Cases with poor appetite had reduced species richness and diversity of their gut microbiome (adjusted OBSERVED: beta = −0.2, P < 0.001; adjusted SHANNON: beta = −0.17, P = 0.0135), significant compositional differences (adjusted non‐parametric multivariate analysis of variance, P = 0.0095), and significant differences in taxa abundance including reduction of genus Lachnospira (logFC = −1.015, q = 0.023). In all‐female subgroup analysis, cases with poor appetite demonstrated reduction in muscle strength (11.03 s vs. 9.26 s, P = 0.02). Conclusions: This study is the first to observe differences in the composition of gut microbiota between healthy community dwelling older individuals with good and poor appetite. We found female individuals with reduced muscle strength had poor appetite compared with those with normal strength. These associations require further examination to understand causality and mechanisms of interaction, to inform potential strategies targeting the gut microbiota as a novel intervention for anorexia of ageing and sarcopenia.